The cubed commutativity degree of dihedral groups - Hamid, M. A. (American Institute of Physics Inc., 2016)
Let G be a finite group. The commutativity degree of a group is the probability that a random pair of elements in the group commute. Furthermore, the n-th power commutativity degree of a group is a generalization of the commutativity degree of a group which is defined as the probability that the n-th power of a random pair of elements in the group commute. In this research, the n-th power commutativity degree for some dihedral groups is computed for the case n equal to 3, called the cubed commutativity degree.